Adaptive correction of the image of an incoherent source object. (February 2019) - Lukin, V.P.
Abstract: The paper examines the operation of an optical system forming an image of an incoherent source object under conditions of atmospheric noise. The effect of atmospheric turbulence is considered. The calculations are performed in the Fresnel – Huygens approximation. The characteristics of the image for 'long' and 'short' exposures are investigated. The issues related to the adaptive correction of the general light wavefront slopes are discussed. The limits of applicability of phase adaptive correction using a reference source are shown.